S87 The effect of on patient comfort and neural respiratory drive (NRD) of ventilator trigger delay during non-invasive ventilation (NIV). (14th November 2013) - Ramsay, MC; Mandal, S; Suh, E-S; Steier, J; Simonds, A; Hart, N
Abstract : Introduction: Optimising patient-ventilator interaction (PVI) has been shown to enhance patient comfort and respiratory muscle unloading. A major cause of poor PVI is ventilator trigger delay, defined as an extended response time in the delivery of airway pressure following initiation of inspiratory effort by the patient. Although bench tests of ventilators have demonstrated variation in trigger response times (120–500ms), there are limited data reporting the effect of trigger delay on a subject's NRD and comfort. We therefore investigated the relationship between ventilator trigger delay, NRD and comfort perception. Methods: A custom-made NIPPY3 + ventilator (B&D Electromedical, Stratford-upon-Avon, UK) with modifiable trigger delay was used. A standardised protocol of 10cm H20 inspiratory positive airway pressure, 4cm H20 expiratory positive airway pressure and back up rate of 6 breaths per minute was utilised in healthy subjects familiarised with NIV. Subjects were blinded to the settings and asked to assess perceived comfort using a visual analogue score (VAS) at 20 randomised trigger delay timings ranging from 10ms to 1000ms following a 2 minute assessment period. Second intercostal space electromyography (EMGpara%max), as a marker of NRD, mask pressure and flow were used to assess PVI. Transcutaneous carbon dioxide and oxygen saturations were controlled within limits of 0.5 kPa and 4% respectively of the subject's baseline values to minimise changes in the biochemical drive to breathe. Results: 5 subjects (1 male) were enrolled to date with a mean age of 34 ± 8years, BMI 22 ± 3kgm 2, FEV1 105 ± 11%predicted and FVC 114 ± 13%predicted. 500 breaths were analysed. The EMGpara%max was lowest at a trigger delay setting of 400ms 5.9%(4.8–8.0) and largest at a trigger delay of 800ms 10.1%(6.0–16.5). (Figure 1 ). There was a corresponding decrease in the VAS score from 78cm (63.5–92.5) at 400ms trigger delay to 47cm (30–66) at 1000ms trigger delay. The highest comfort score was 89cm (52–92) observed at 170ms trigger delay. Conclusion: This is the first study to comprehensively investigate NIV trigger delay in healthy subjects. Based on NRD, these data suggest that the optimal NIV trigger response time was up to 400ms. This challenges previous bench studies that reported ventilators with response times over 100–150ms have limited clinical utility.